Enhancing interfacial properties of carbon fiber/polyamide 6 composites by in-situ growing polyphosphazene nanotubes - X. Q. Zhang; G. L. Hu; L. Cen; C. H. Lei (eXPRESS Polymer Letters)
We explored a simple approach to grow needle-like polyphosphazene nanotubes (PZSNT) on carbon fibers (CFPZSNT) via in-situ polycondensation under mild reaction conditions, to form a PZSNT-based multiscale reinforcement. PZSNT with abundant free hydroxyl groups can significantly change the chemical surface and increase the specific surface area of carbon fibers. A significant improvement of interfacial shear strength was obtained from 39.7 MPa for the virgin CF/polyamide 6 composites to 69.6 MPa for the CF-PZSNT/polyamide 6 composites.